2017
DOI: 10.1002/csr.1393
|View full text |Cite
|
Sign up to set email alerts
|

CSR Strategy in Technology Companies: Its Influence on Performance, Competitiveness and Sustainability

Abstract: In this paper, a structural equation model is presented to study the adoption of a strategy of Corporate Social Responsibility (CSR) within the Spanish technological industry sector, and how this strategy may influence its performance, competitiveness, and sustainability. For that reason, a survey was submitted to technology companies located in Spanish Science and Technology parks. The study shows that a CSR‐oriented strategy contributes significantly to the performance of the organisation. Moreover, CSR infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 57 publications
4
76
0
2
Order By: Relevance
“…While others have considered R&D investments, ability to differentiate products, advertising intensity, growth rate and corporate governance systems, this paper adopts a sectoral perspective, focusing specifically on the ICT industry. If an industry requires relatively intensive stakeholder management, or if a sector faces severe competition and rapidly changing market trends that require constant renovation to achieve competitive advantages, the benefits of CSP are maximized, because if integrated into business processes in this case CSP generates innovative practices, which improve competitiveness (Bernal‐Conesa et al ., ). The ICT industry has been leading the market with a strong momentum for growth and relies heavily on R&D innovation and advertising.…”
Section: Literature Review and Hypothesis Development For The Relatiomentioning
confidence: 97%
“…While others have considered R&D investments, ability to differentiate products, advertising intensity, growth rate and corporate governance systems, this paper adopts a sectoral perspective, focusing specifically on the ICT industry. If an industry requires relatively intensive stakeholder management, or if a sector faces severe competition and rapidly changing market trends that require constant renovation to achieve competitive advantages, the benefits of CSP are maximized, because if integrated into business processes in this case CSP generates innovative practices, which improve competitiveness (Bernal‐Conesa et al ., ). The ICT industry has been leading the market with a strong momentum for growth and relies heavily on R&D innovation and advertising.…”
Section: Literature Review and Hypothesis Development For The Relatiomentioning
confidence: 97%
“…Furthermore, scholars have identified that these benefits accrue because CSR fosters greater unity, a sense of belonging, and a firm's ability to attract and retain high‐quality staff (Gupta & Hodges, ; Klimkiewicz & Oltra, ; Story, Castanheira, & Hartig, ; Supanti, Butcher, & Fredline, ). Other reported benefits of incorporating CSR include: increase in sales, cost reduction, less need for government to promote CSR activities, efficiency gains from environmentally friendly technologies, competitiveness, and reduced cost of capital (Bernal‐Conesa, Nieves Nieto, & Briones‐Peñalver, ; Bhattacharya, Sen, & Korschun, ; Mishra & Suar, ; Supanti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is common to link the study of CSR with the innovation undertaken by a company because CSR is, in itself, an innovation [68,77], and furthermore it is a mechanism that facilitates innovation [13,78,79]. CSR is an efficient business strategy that penetrates every innovative organization and becomes a key element in differentiating between competitors [68,80].…”
Section: Csr the Supply Chain And Innovation In Smesmentioning
confidence: 99%
“…At first, it was large companies that addressed the implementation of socially responsible actions [44,[63][64][65], although later, small and medium-sized companies (SMEs) began to address this strategy [66][67][68]. The progress that the SMEs have shown in this sense is important given that they constitute the true motor of economic growth and are generators of value in the territories [69][70][71].…”
Section: Csr the Supply Chain And Innovation In Smesmentioning
confidence: 99%
See 1 more Smart Citation